The mathematics of diffusion. 2nd Edn. - Crank, J.
Contents: The diffusion equations; methods of solution when the diffusion coefficient is constant; Infinite and semi-infinite media; Diffusion in a plane sheet; Diffusion in a cylinder; Diffusion in a sphere; Concentration-dependent diffusion-methods of solution; numerical methods; Some calculated results for variable diffusion coefficients; The definition and measurement of diffusion coefficients; Non-Fickian diffusion; Diffusion in heterogeneous media; Moving boundaries; Diffusion and chemical reaction; Simultaneous diffusion of heat and moisture.
Keywords: DIFFUSION; MATHEMATICS